South & Central America and the Caribbean - Kaenzig, Raoul (Geneva: International Organization for Migration (IOM), 2014)
This chapter is based on existing empirical studies related to climate change and migration in Latin America and the Caribbean. It looks at the situation in the region as compared with that in other regions of the world, while underscoring certain aspects that are specific to Latin America and the Caribbean. Historical analogy is used; a summary of the past consequences of environmental degradation for migration facilitates an evaluation of the future consequences of climate change. In addition, this compilation of existing studies also makes it possible to reflect critically on the geographic and theoretical distribution of the case studies and to identify the regions for which additional and complementary studies would be desirable, given the vulnerability of those regions. Based on the existing literature, three kinds of climate evolution are expected to have the greatest impact in terms of population displacement: natural hazards (tropical cyclones, heavy rains and floods), droughts and sea level rise. Added to this list is the melting of glaciers, which is a particularly sensitive issue in South America. The present chapter includes an evaluation of the impact on migration of each of these phenomena based either on historical experience or on projections.
Keywords: Climate change; Migration; Environmental migrants; Latin America; Caribbean